Simple cultivation of effective microorganisms to reduce number of flies in local chicken coop / Wan Siti Atikah Wan Omar and Muzammil Izzat Arbain - Wan Omar, Wan Siti Atikah; Arbain, Muzammil Izzat (Universiti Teknologi MARA Cawangan Pahang, 2019)
Effective microorganisms (EM) were used in many biological applications, such as the making of organic fertiliser and bioremediation. Some chicken farmers make their effective microorganisms due to simple preparation and to reduce the production cost. However, the effectiveness of the EM in an actual chicken coop was hardly found reported. In this research, the effectiveness of a commercial EM (EM-1) was compared with self-prepared EM made from the fermentation of pineapple (EM-Pineapple) and milk (EM-Milk). This experiment was run at a chicken coop with a capacity of 100 chickens. The number of flies in the coop was collected and counted before, and after the EM was sprayed in the chicken coop. After-treatment, EM-1 reduced flies’ number about 62.27%. EM-Milk decrease flies’ number to 55.00% while EM-Pineapple reduces the flies to 50.34%. Although all the EM showed a reduction of flies’ number after the treatment, EM-1 is the most effective compared to other EMs. However, statistical analysis shows that the effectiveness among the treatments is similar. This finding suggested that simple cultivation of EM can prevent foul odour and economically reduces the number of flies in the small-scale chicken coop